Vegetation Association and Site Preferences of Tongkat Ali (Eurycoma Longifolia Jack) in a Health Lowland Forest, Pahang, Malaysia - Ibrahim, Zahari (2005)
Tongkat Ali (Eurycoma longifolia Jack) is one of the most popular medicinal plants and is gaining greater recognition in Malaysia. Currently, E. longifolia is being over-exploited due to its high popularity as a potential herbal medicine and high demand in the market. Thus, this study on the species site preferences of E. longifolia is necessary to ensure successful conservation of the species. There have been no studies reported on the ecological requirements, vegetative association, microclimate and site-suitability of E. longifalia. The objectives of this study are to identify the vegetative association and tree species composition of E. longifolia in its natural habitat; to determine the relationship between these plant associations and the soil characteristics and to determine the relationship between foliar nutrient concentrations and density of E. longfolia. The study was carried-out in a heath lowland forest, located in Compartments 6 and 10 of Menchali Forest Reserve, Rompin, Pahang. A total of 20 vegetation samples (relevk), each with the size of 30 m x 30m (900m2) were established in Compartment 6 (secondary forest) and Compt. 10 (primary forest) and were classified into four groups based on coverage density of E. longifolia vis, rare (El), low (E2), moderate (E3) and high (E4). This study is basically a phytosociological study using the design primarily based on the Braun Blanquett Method (1964). A quantitative study of the vegetation layer namely dominant (TI), understorey (T2), shrub (S) and Herbs (H)) were recorded from 900m2 releves to include species composition , association , diversity and plant communities of this area. The environmental variables viz soil temperature, moisture content, pH, bulk density, particle density, soil nutrients, organic matter, soil micronutrients, light intensity and altitude were also analyzed and recorded for each relev&. In addition, foliar analysis of E. longfolia and shrub species was also done. The results revealed that there are 207 species of trees, shrubs, herbs, ferns and herbaceous plants representing 74 families and 155 genera. It also found that there are seven types of life forms in Menchali Forest Reserve, namely woody plant, ferns, moses, climbers, palms, herbaceous and ephiphytes, whereas the woody plants are the most abundant constituting of 53.2% by family 62% by genera and 61% by species.Eurycoma longifolia, Brackenridgea palustris, Garcinia nigrolineata, Syzygium syzygioides, Diospyros styraciformis, Ardisia crenata, Dipterocarpus chartaceus, Calophyllum canum, Psydrax maingayi, Memecylon edule, Shorea materialis, Vatica pauciflora, Champereia manillana, E ythroxyllum cuneatum, Guioa pleuropteris, Tetracera indica, Syzygium campanulatum and Licuala spinosa were among the common species in the study area. These were differentiated into two differential communities of Vitex pinnata-Bouea macrophylla and Xanthophyllum wrayi-Bromhaedia finlaysoniana. The two communities constituted sixteen sub-communities which represent the association species of E. longifolia. The results of soil analysis showed that most of the soil physical and chemical properties were significantly different ( ~ ~ 0 . 0a5m)o ng the cluster groups such as total nitrogen (N), total phosphorus (P), calcium (Ca), sodium (Na), magnesium (Mg), copper (Cu), zinc (Zn) and soil pH. -The correlation analysis between the soil parameters and density of E. longifolia showed that the soil parameters influenced the distribution of this species are moisture content, soil pH, Total P, Ca, Cu, Zn, Mn and Fe. Foliar nutrient concentrations are not significantly different among the cluster groups except for Mn and Zn. Light intensity in Group El recorded the highest value in light intensity (4012 lux) while the lowest value was in Group E4 (1651.71 lux). The light intensity was significantly different (P10.05) among the cluster groups. This indicates that the distribution of E. longifolia was mainly as understorey growth and is considered as a shade-tolerant species. Relationship between species and environmental variables showed that light intensity, soil moisture content, pH, texture (%), total P, calcium, copper and zinc were among the important factors in the distribution of the vegetation in Menchali forest. This implies that the site preferences and density of E. longifolia was also influenced by these factors. The results of this study also showed the usefulness of phytosociological study in the development of community association of similar species growing in heath lowland forest. It is useful to develop association community of E. longifolia in the heath lowland forest, and to provide valuable information for rehabilitation, conservation and restoration of E. longifolia.